PENGARUH METODE HYPNOTEACHING TERHADAP HASIL BELAJAR IPS KELAS IV UPT SDN 69 GALESONG I KABUPATEN TAKALAR - Kartika; Nursalam; Yumriani (STKIP Subang, 2025)
Kartika 2025. The Effect of Hypnoteaching Method on Social Studies Learning Outcomes of Grade IV Students of UPT Sdn 69 Galesong I, Takalar Regency. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Prof. Dr. H. Nursalam, M.Si and supervisor II Dr. Yumriani, S.Pd, M.Pd.Based on the background, it explains that choosing the right learning method makes students more enthusiastic in learning so that it is expected to obtain maximum learning outcomes and provide a positive impact. Therefore, based on the background above, the researcher needs to conduct a study entitled